Migration to solar water pump system: Environmental and economic benefits and their optimization using genetic algorithm Based MPPT. (November 2022) - Hilali, Abdelilah; Mardoude, Yahya; Essahlaoui, Ali; Rahali, Abderrafii; Ouanjli, Najib El
Abstract: The amount of rainfall in Meknes region in Morocco is insufficient to meet agricultural water demand. Pumping methods based on diesel and butane are thus an unavoidable option for local farmers. Nonetheless, the region receives an average of 4.72 kW.m −2 .day −1 of solar irradiation per day, thus solar pumping systems can cover irrigation needs while also provide other benefits such as lowering greenhouse gas emissions, minimizing energy expenditures, and aiding in environmental preservation. Farmers in the Meknes region, on the other hand, are hesitant to employ photovoltaic energy to power their equipment. This work has two aims: the first is to explore the solar energy resource in the region. This is to analyze the capacity of the energy resource to adequately meet the energy needs of solar water pumping systems in the region. Secondly, based on the coupling theory, a comparative study was conducted. The objective was to evaluate the two methods of operation of solar systems, namely direct coupling and coupling with a DC–DC adapter with a genetic algorithm. The findings of this study reveal that with this adaptation stage, this solution doubles energy efficiency.